(untitled) (Bangladesh Medical Journal, 2024)
Spontaneous Bacterial Peritonitis (SBP), an infection of ascitic fluid without demonstrable intra-abdominal origin and it is a complication of cirrhosis of liver, with a reported mortality of 30% to 50% in adults. The counts of polymorphonuclear leucocytes (PMN) in ascitic fluid ≥250/mm² demonstrably confirms the diagnosis of SBP and the patients immediately need treatment with antibiotics irrespective of culture results. Serum C- reactive protein (CRP) is a reliable predictor of SBP and a marker that can be measured in several laboratories. The aim of this study was to estimate serum C-reactive protein levels as a diagnostic tool for evaluation of SBP in patients with liver cirrhosis and ascites. This cross-sectional study was conducted among 90 adult patients diagnosed as cirrhosis of liver with ascites in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period November 2017 to March 2019. Half of the patients were at their productive age (≤30 to 50 years) and others were above 50 years with mean age of 50.5 years; where male female ratio was about 2.5:1. The study found that more than one-fifth (21.1%) of the patients had SBP positive (SBP group) and their mean serum CRP was found 84.59±39.66mg/L; on the other hand rest of the patients were SBP negative (non-SBP group) with mean serum CRP was 15.02 ± 18.34 mg/L. The mean total WBC count and neutrophil count in ascitic fluid were found 2565 ± 3439/mm³ and 1255 ± 1708/mm³ in SBP patients; where 178 ± 149/mm³ and 46 ± 38/ mm³ in non-SBP patients respectively. At the serum CRP cut-off level of 41.5 mg/L, the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 89.5%, 94.4%, 81% and 97.1% respectively. In the diagnosis of SBP based on PMN 2250/mm³, the accuracy of the test result was 93.3% and based on ascitic fluid culture results it was 78.9%. It is vital to assess the utility of CRP in diagnosis of SBP in cirrhosis of liver with ascites. At the optimal cut-off level of 41.5 mg/L, the serum CRP value had the good sensitivity (89.5%), specificity (94.4%), and AUC-ROC (0.969) in diagnosis of SBP. Large scale analytical studies on cirrhotic patients with ascites are encouraged to establish the optimum cut-off value of CRP for the diagnosis of SBP. Bangladesh Med J. 2023 Sept; 52(3): 14-26